Uncovering Hidden Meaning in IKEA Advertisement “Home is a Different World”: A Semiotic Analysis - Ayu Trisna Dewi Gusti Agung; Ni Wayan Suastini; I Wayan Juniartha (Yavana Bhasha : Journal of English Language Education, 2022)
ABSTRACT Advertisement has a function to create brand awareness, products, services and ideas, that can convince customers if the company’s services or products ideas are best to buy. The IKEA advertisement aims to provide information to the people about how to make furniture with good function and design affordable for everyone. Furthermore, this study combines verbal and visual signs to give the advertisement a certain effect. This study is aimed to describe the hidden meaning that can be found in IKEA advertisement “Home is a Different World”. This study uses Semiotics theory by Saussure cited in Chandler (2007) and theory of meaning by Barthes (1967) that is supported by the theory of color terms proposed by Wierzbicka (1996). The data were collected through the observation method. The descriptive qualitative method is used to analyze the data in this study. The study concludes that both verbal and visual signs found in each data carry a hidden meaning. In general, the advertisement conveys the meaning to encourage the audience to promote their product by giving a nice ideas to make a good home design and get better life at home by creating meaningful moments with our family at home.